Principles of geotechnical engineering - Das, Braja M. 1941-; Sobhan, Khaled (Cengage Learning, 2018)
Gain a solid understanding of soil mechanics and soil properties as Das and Sobhan's PRINCIPLES OF GEOTECHNICAL ENGINEERING, SI EDITION, 9E introduces these topics together with coverage of field practices and basic civil engineering procedures. This book provides the important foundation that you need for future studies in your design-oriented courses and in professional practice. This book ensures a practical approach by incorporating a wealth of comprehensive discussions and detailed explanations. PRINCIPLES OF GEOTECHNICAL ENGINEERING, SI EDITION, 9E provides more figures and worked-out problems than any other book for the course to further ensure your understanding.